Variability of black carbon deposition to the East Antarctic Plateau, 1800–2000 AD - Bisiaux, M.; Edwards, Peter; McConnell, J.; Albert, M.; Ansch¨ utz, H.; Neumann, T.; Isaksson, E.; Penner, J. (Copernicus Publications, 2012)
Refractory black carbon aerosols (rBC) from biomass burning and fossil fuel combustion are depositedto the Antarctic ice sheet and preserve a history of emissions and long-range transport from low- and mid-latitudes. Antarctic ice core rBC records may thus provide information with respect to past combustion aerosol emissions and atmospheric circulation. Here, we present six East Antarcticice core records of rBC concentrations and fluxes covering the last two centuries with approximately annual resolution (cal. yr. 1800 to 2000). The ice cores were drilled in disparate regions of the high East Antarctic ice sheet, at different elevations and net snow accumulation rates. Annual rBC concentrations were log-normally distributed and geometric means of annual concentrations ranged from 0.10 to 0.18 µg kg-1. Average rBC fluxes were determined over the time periods 1800 to 2000 and 1963 to 2000 and ranged from 3.4 to 15.5 µgm-2 a-1 and 3.6 to 21.8 µgm-2 a-1, respectively. Geometric mean concentrations spanning 1800 to 2000 increased linearly with elevation at a rate of 0.025 µg kg-1/500 m. Spectral analysis of the records revealed significant decadal-scale variability, which at several sites was comparable to decadal ENSO variability.